Global incidence, risk factors, and temporal trends of nasal cancer: A population‐based analysis - Junjie Huang; Wing Sze Pang; Fung Yu Mak; Sze Chai Chan; Veeleah Lok; Lin Zhang; Xu Lin; Don Eliseo Lucero‐Prisno III; Wanghong Xu; Zhi‐Jie Zheng; Edmar Elcarte; Mellissa Withers; et al. (Cancer Medicine)
Abstract Background Nasal cancer is a rare and fatal disease, with an incidence rate of <1 in 100,000, and a 5‐year survival rate of around 30%. The study aims to investigate the worldwide disease burden, associated risk factors, and temporal incidence patterns of nasal cancer. Methods Data were obtained from multiple sources, including the Global Cancer Observatory, Cancer Incidence in Five Continents Plus, the Global Burden of Disease database, the World Bank, and the United Nations. The study utilized multivariable linear regression to investigate the relationship between risk factors and the incidence of nasal cancer by age for each country. Trend analysis was conducted using the joinpoint regression analysis program, and the average annual percentage change (AAPC) was calculated. The accuracy of trend estimations was assessed using the 95% confidence interval (CI). Additionally, the incidence of nasal cancer was examined by age and geographic location. Results A total of 37,674 new cases were reported in 2020 (ASR 4.2 per 1,000,000). The highest ASRs were observed in South‐Eastern Asia (5.3) and Central and Eastern Europe (4.8). A number of risk factors were identified, such as higher HDI regions, higher prevalence of smoking, alcohol drinking, unhealthy dietary, and hypertension. In addition, physical inactivity was related to lower incidence. An overall decreasing trend was reported in the global population, but an increasing trend was discovered in males. Conclusions The highest burden of nasal cancer was found in South‐Eastern Asia and Central and Eastern Europe, potentially due to regional genetic factors and pollution issues. Targeted interventions are need in high‐risk regions. Further studies are needed to investigate factors contributing to the increasing temporal trend of nasal cancer among the male population.